Making Futures workshop - Koutsomichalis, Marinos (My University, 2022)
16 aeons ago humans living on planet Earth decided to abandon language. You are these humans’ mute descendants, currently inhabiting a suspended timespace with a finite edge. In order to ensure your survival you must return to Earth, but before, you must unveil the mysteries of this decision and steer a path toward new futures.